Comparação entre curvas típicas e curvas medidas de carga de metalúrgicas alimentadas em média tensão - Dalla Palma, Elisa Pinheiro (My University, 2021)
The rise of the electricity sector in Brazil is due to the significant increase in energy consumption in recent decades. Technical and economic planning by energy providers and distributors is extremely important, so that it is possible to make the electricity sector more efficient every day. The analysis of the typical load curves allows a better quality of energy to be delivered, helping in the calculation of losses, demand forecast, future voltage levels in a given location, lower tariffs and higher investments. Because Brazil has an extensive territory, each region has it's particular characteristics, so adapting the typical load curves to each reality is essential. Industry is currently responsible for 34.8% of electricity consumption in Brasil, with 23.5% of the energy used in the industrial sector being consumed by metallurgy. From this approach, typical load curves of metallurgical plants serviced at medium voltage were compared with electric transformers of 300kVA, 500kVA and 750kVA carried out in industries with the same characteristic in Caxias do Sul. For the utilization factor, the highest percentage error between the typical value and the measured value was obtained in metallurgical plants that have a 500kVA power transformer, reaching the measure of 51.79% error. The 300kVA metallurgical plants presented an error of 37.67% for the utilization factor and the 750kVA ones presented an error of 31.80%. As for the load factor, the highest percentage error between the typical value and the measured value was obtained in metallurgical plants that have a 750kVA power transformer, reaching 15.76% error. The 300kVA metallurgy plants had a low error of 3.06% for the utilization factor and the 500kVA ones had an error of 11.41%. Correction coefficients were generated for each of the five levels of demand, according to stratification, using the standardization in which the error was smaller, using the maximum demand one. For the 300kVA metallurgical companies, the most significant coefficient proposed was that of the fourth level, in the value of 0.524, changing the new value to 52.4% of the old value. As for the 500kVA metallurgy companies, the most significant coefficient proposed was that of the fifth level, with a value of 1.951, and for those of 750kVA it was that of the fifth level, with a value of 2.012. It was found that the typical load curves of metallurgical plants served at medium voltage need to be adapted according to each reality, especially the first, fourth and fifth levels. [resumo fornecido pelo autor]
A ascensão do setor elétrico no Brasil, se dá pelo aumento significativo do consumo de energia nas ultimas décadas. O planejamento técnico e econômico por parte das concessionárias e distribuidoras é de extrema importância, para que seja possível tornar o setor elétrico cada dia mais eficiente. A análise das curvas típicas de carga possibilita uma maior qualidade na entrega de energia, auxiliando nos cálculos de perdas, previsão de demanda, níveis de tensão futuros em determinado local, tarifas e investimentos. Pelo Brasil possuir um território extenso, cada região possui características particulares, então adequar as curvas típicas de carga para cada realidade é fundamental. Atualmente a indústria é responsável por 34,8% do consumo de energia elétrica no Brasil, sendo que 23,5% da energia utilizada no ramo industrial é consumida por metalúrgicas. A partir dessa abordagem, a proposta deste trabalho foi comparar as curvas típicas de carga de metalúrgicas atendidas em média tensão, que possuem transformador elétrico de 300kVA, 500kVA e 750kVA com medições efetuadas em indústrias de igual característica em Caxias do Sul. Para o fator de utilização, o maior erro percentual entre o valor típico e o valor medido foi obtido nas metalúrgicas que possuem transformador de 500kVA de potência, chegando a 51,79% de erro. As metalúrgicas de 300kVA apresentaram um erro de 37,67% para o fator de utilização e as de 750kVA um erro de 31,80%. Já para o fator de carga, o maior erro percentual entre o valor típico e o valor medido foi obtido nas metalúrgicas que possuem transformador de 750kVA de potência, chegando a 15,76% de erro. As metalúrgicas de 300kVA apresentaram um erro baixo de 3,06% para o fator de utilização e as de 500kVA um erro de 11,41%. Foram gerados coeficientes de correção para cada um dos cinco patamares de demanda, conforme estratificação, utilizando a padronização em que o erro foi menor, a da demanda máxima. Para as metalúrgicas de 300kVA, o coeficiente proposto mais significativo foi o do quarto patamar, no valor de 0,524, alterando o novo valor para 52,4% do valor antigo. Já para as metalúrgicas de 500kVA, o coeficiente proposto mais significativo foi o do quinto patamar, no valor de 1,951 e para as de 750kVA foi o do quinto patamar, no valor de 2,012. Foi constatado que as curvas típicas de cargas de metalúrgicas atendidas em média tensão necessitam ser adequadas conforme cada realidade, principalmente o primeiro, quarto e quinto patamar. [resumo fornecido pelo autor]
Keywords: Engenharia elétrica; Metalúrgicas; Energia elétrica - Distribuição